14x+7=-6x-43

Simple and best practice solution for 14x+7=-6x-43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14x+7=-6x-43 equation:


Simplifying
14x + 7 = -6x + -43

Reorder the terms:
7 + 14x = -6x + -43

Reorder the terms:
7 + 14x = -43 + -6x

Solving
7 + 14x = -43 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
7 + 14x + 6x = -43 + -6x + 6x

Combine like terms: 14x + 6x = 20x
7 + 20x = -43 + -6x + 6x

Combine like terms: -6x + 6x = 0
7 + 20x = -43 + 0
7 + 20x = -43

Add '-7' to each side of the equation.
7 + -7 + 20x = -43 + -7

Combine like terms: 7 + -7 = 0
0 + 20x = -43 + -7
20x = -43 + -7

Combine like terms: -43 + -7 = -50
20x = -50

Divide each side by '20'.
x = -2.5

Simplifying
x = -2.5

See similar equations:

| 2(6t+1)-4=t-(t+1) | | 9c-4y=0 | | (5+2x)*4=5+8x | | 20/x=100 | | 6x=150 | | 7*8,333...-23=4*8,333...+2 | | 9x+4y+7z-5x+4z-5y= | | -5x-9=11-6x | | 35+x=27 | | 7x/4=14 | | 7x-23=4x+2 | | 7x-23=4x | | -6=9x+3 | | 1-5x+(2+x^2)x^2=0 | | x+4.7=63 | | 30=3x-3 | | 5x+5y=260 | | 1/2+4/5 | | x*5=300 | | 1/2+24/5 | | 3x+(4x+5)=180 | | x+2x+(7x+2)=22 | | 31/2+p=51/4 | | (X+3)(x+3)=100 | | 3u=42-4u | | 5(n-3)-3=12 | | 12-1*0+4/2 | | x-9/5+1/5=-x/15 | | x/6.5=4 | | 13+7m=97 | | c^2=-6-5c | | x-16=24 |

Equations solver categories